Active Tectonics of Hamedan Area, West Iran - Chegini, Atefeh; Sorbi, Ali; Arian, Mehran (International Journal of Geography and Geology, 2015)
Hamedan area has located in the Sanandaj-Sirjan belt in the west Iran. Geomorphic indices of active tectonics are useful tools to analyze the influence of active tectonics. These indices have the advantage of being calculate from Arc GIS and remote sensing packages over large area as a reconnaissance tool to identify geomorphic anomalies possibly related to active tectonics. This is particularly valuable in where relatively little work on active tectonics based on this method was done, so this method is new and useful. Six geomorphic indices were calculated in the study area. Through averaging these indices we obtain index of active tectonics (Iat). The values of the index were divided into classes to define the degree of active tectonics. Therefore, relative tectonic activity was calculated and their values were classified and analyzed in three groups. The low class of Iat is mainly in the sub-basins of 1,7,10,11,16,22,24, 27&28 While the rest of the study area has moderate active tectonics in the sub-basins of 2 ,3 ,4 ,5 ,6 ,8 ,9 ,12 ,13,14,15,17,18,20,21,23,25,26 and high in the sub-basins of 19. Our results show that the moderate value has located along faulted area, which shows 3 class of relative tectonic activity.